Effect Service Quality, Discount, Social Media Marketing Interactivity on Shoppers’loyalty with Online Trust as Intervening Variable User Reny Swalayan-Ku Surabaya - Soniya Auliya Sabilah Hakiki; Nurul Azizah (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
The company distinguishes itself from other retail stores through its unique approach, particularly in managing minimarkets by adhering to sharia principles in employee management. Ecommerce Reny Swalayan-ku merges traditional self-service elements with modern technology, positioning itself as a platform that facilitates the online purchase of daily necessities. The platform features user-friendly mobile applications and websites designed to streamline transactions, offering a variety of flexible payment options to enhance the shopping experience. Furthermore, goods are delivered using Reny Swalayan-ku own expedition service, with shipping costs calculated based on the distance from the customer's home to the minimarket. This research seeks to examine the impact of Service Quality, Discounts, and the Interactivity of Social Media Marketing on Shoppers’loyalty, with Online Trust serving as an intervening variable among users of Reny Swalayanku in Surabaya. An associative quantitative research methodology was employed, utilizing data gathered via questionnaires distributed to 94 respondents who are users of Reny Swalayan-ku Surabaya. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) through the SmartPLS software. The findings of the research suggest that Service Quality, Discounts, and the Interactivity of Social Media Marketing have a significant and positive impact on Online Trust. Additionally, Online Trust was determined to exert a positive and significant effect on Shoppers’loyalty. Moreover, both Discount and Social Media Marketing Interactivity directly and positively influence Shoppers’loyalty. In contrast, Service Quality does not demonstrate a significant direct impact on Shoppers’loyalty, indicating that its function may primarily serve as a foundation for establishing trust, which subsequently affects loyalty. These results highlight the critical role of fostering consumer trust through high-quality service, appealing discount promotions, and engaging social media interactions to enhance Shoppers’loyalty within the realm of retail e-commerce.